An investigation of the rehabilitation needs, development, and preliminary outcomes of an education and exercise self-management intervention for breast cancer survivors - Beutel, Anita (Division of Physiotherapy, 2025)
An investigation of the rehabilitation needs, development, and preliminary outcomes of an education and exercise self-management intervention for breast cancer survivors. The central premise of this thesis was that breast cancer (BC) survivors face debilitating long-term side effects (LTSEs) after completing their medical cancer treatment (MCT), such as chronic pain and upper limb dysfunction, cancer-related fatigue, a reduction in health-related quality of life (HRQoL), reduced physical function, weight gain, and lymphoedema. It was hypothesised that BC survivors may not receive education and support to manage these and other LTSEs. It was also hypothesised that LTSEs of BC treatment can be improved by an education and exercise self-management intervention (SMI). Firstly, a qualitative study using focus group discussions was conducted to investigate the lived experience of LTSEs of BC treatment and the rehabilitation needs of survivors, in a semi-urban region of South Africa (SA)(n = 23). The findings of the qualitative study revealed that survivors were affected by LTSEs of MCT. These impacted their daily lives, and in some cases, the ability to provide for their families. Participants were unable to self-manage their symptoms as they had not been provided with information or rehabilitation for these sequelae of their cancer. Furthermore, many participants lacked support from cancer support organisations, and felt isolated. Transportation and financial challenges were identified, and survivors lived in geographically diverse areas. Attitudes towards and perspectives of participating in a rehabilitation intervention including an exercise component, were positive. However, specific exercise and rehabilitation preferences varied between participants. For example, some participants preferred to exercise in a group, while others preferred to exercise alone, or with a family member. Some participants preferred to receive survivorship information via email or through printed material, while others preferred to receive talks. Second, a systematic review and meta-analysis was conducted to determine the effectiveness of SMIs including an exercise component, to improve LTSEs and physical activity, in BC survivors following the completion of MCT. The systematic review and meta-analysis presented in this thesis (n = 10 studies) found that, as an alternative to supervised on-site interventions, SMIs including an exercise component are effective to improve LTSEs and increase physical activity, in early-stage BC survivors following MCT. Third, the results of the qualitative study and the systematic review were used to inform the content and structure; and the Medical Research Council (MRC) guidelines for intervention development were used to inform the process of developing an education and exercise SMI. As patient-centred SMIs based on cognitive behavioural and self-management principles have shown promise in previous chronic disease management programmes, the new intervention ‘Survive and Thrive' was informed by the abovementioned principles. Content validation was established by obtaining feedback from a multidisciplinary team of five South African clinical BC experts and refining the intervention accordingly. An acceptability evaluation was conducted through a small qualitative study including three BC survivors. Alterations were made to the intervention according to the results of this study. The final phase was a single-group, pre-test-post-test study (n = 33) to determine the feasibility, safety, and preliminary outcomes of the newly developed intervention, in early-stage BC survivors who had completed their MCT. The baseline findings of the intervention study suggest that prevalence and levels of pain and cancer-related fatigue were high, and HRQoL index scores and physical activity levels were low at baseline, compared to previous studies of BC survivors conducted in high-income countries. The intervention was feasible and safe to implement in this study. Furthermore, significant improvements were demonstrated post-intervention in terms of pain and fatigue prevalence, severity, and interference, HRQoL, self-efficacy, and exercise participation. The findings of this thesis revealed that physical LTSEs were a significant problem for South African BC survivors, and that they were largely unaddressed by the standard of care. Further, the findings demonstrated that a resource-efficient SMI was feasible, safe, and potentially effective to improve patient-reported outcomes in South African BC survivors.